LAYANAN PEMBELAJARAN BAGI SISWA AUTISME DI SEKOLAH PENYELENGGARA PENDIDIKAN INKLUSIF - M. Iqbal (Universitas Negeri Padang, 2014)
Abstrak : This study discusses the service learning for school students Autism in inclusive education providers. The purpose of this study is to describe how the implementation of services for students Autism that is given by 4 SMK Padang which is a regular school and be an inclusive school organizers. This study used a qualitative descriptive approach through techniques of data collection through interviews, observation and documentation. The results showed that the school is not providing maximum service to the Autism students and teachers do not understand how inclusive education for children with special needs. Kata Kunci : Siswa Autisme; Layanan Pembelajaran; Pendidikan Inklusif